Sleep quality and academic performance of nursing students - Aung, Khin Thandar; Nurumal, Mohd. Said; Zainal, SitiNurhizwany (www.iosrjournals.org, 2016)
Quality of sleep is one of the important elements of the learning process and memory. However, sleep problems are prominent among college students, which could affect their academic performance. The aim of this study wasto identify the association between quality of sleep and its impact towards academic performance among nursing students at the Faculty of Nursing in International Islamic University, Malaysia (IIUM). A quantitative, cross-sectional study was conducted in the Facultyof Nursing at Jalan Hospital Campus. There were 105 nursing students involved as participants and they were selected by using the convenience sampling method. The questionnaires consisted of three parts; Socio-demographic (age, gender, level of study and participation in extracurricular activities), Pittsburgh Sleep Quality Index (PSQI) and Academic performance (GPA). About 48.6% out ofa total of 105 nursing students had a PSQI score of five and more which means ‘good sleep quality’ and 51.4% had a score of less than 5 which means ‘poor sleep quality’. The result showed that there was a significant association between sleep quality and academic performance. The findings provide information regarding sleep quality of students in the Faculty of Nursing and its impact towards academic performance. Thus, it is recommended for responsible parties to design and implement appropriate interventions to improve sleep quality for academic performance enhancement.